PENGARUH MOTIVASI BELAJAR DAN KESIAPAN BELAJAR TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN SEJARAH KELAS XI-IIS SMA NEGERI 1 PRAJEKAN SEMESTER GANJIL TAHUN PELAJARAN 2015/2016 - Dyan Yuliana (STKIP PGRI SITUBONDO, 2016)
In the educational process the emphasis lies on the part of students that will be a process of learning which the interaction with experiences. Learning resulted in a change in those who learn. Such changes are integral, meaning that changes in cognitive, affective, and psychomotor. According to the theory, the cognitive aspects can be influenced by students' learning readiness. Conditions of students who are ready to receive lessons from teachers, will try to respond to the questions that have been given by the teacher. This study aims to determine whether there is influence intrinsic motivation, extrinsic motivation and readiness to learn students' learning outcomes of students. This research is quantitative. Methods of data collection were questionnaires, tests, and documentation. The subjects were students of class XI IIS with a population of 65 students. Data analysis includes the correlation and analysis of variance fatherly all variables. Hypothesis test to determine the effect of intrinsic motivation, extrinsic motivation and readiness to learn students' learning outcomes of students with the results of F = 14.241, F table = 3.94 at α = 0.05. Turns of F = 14.241> F table = 3.94. For R Square obtained 41.189%, we conclude that there is the influence of intrinsic motivation, extrinsic motivation and readiness to learn students' learning outcomes of students with the effective contribution of 41.189%. Effective contribution (SE) predictor (X1) intrinsic motivation to criterion (Y) student learning outcomes 9.381%, Effective Contribution (SE) Predictor (X2) extrinsic motivation to criterion (Y) 0.830% student learning outcomes, Contribution Effective Predictor (X3) student learning readiness to criterion (Y) 30.978% of student learning outcomes of this study indicate that the readiness of students more influence on student learning outcomes than the motivation to learn. By looking at the results of the data which has been described previously, it can be concluded that